Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

PLEASE ANSWER ASAP!!
Use completing the square to rewrite the function in vertex form. f(x) = x² + 4x - 7
○ f(x) = (x+2)² - 11
Of(x) = (x-7)² +4
○ ƒ(x) = (x+2)² – 3
○ f(x) = (x − 2)² – 7


Sagot :

Answer:  Choice A

f(x) = (x + 2)^2 - 11

=========================================================

Work Shown:

y = x^2 + 4x - 7

y+7 = x^2 + 4x

y+7+4 = x^2 + 4x + 4

y+11 = x^2 + 4x + 4

y+11 = (x + 2)^2

y = (x + 2)^2 - 11

f(x) = (x + 2)^2 - 11

In the third step, I added 4 to both sides to complete the square for the x^2+4x portion. Notice that (x+2)^2 = x^2+4x+4. So I added 4 to fill in the missing piece needed to complete the square.

Put another way the '4' added to both sides is because we first divided the x coefficient 4 in half to get 4/2 = 2. Then you square it to get 2^2 = 4.

--------------------

Alternative Method (optional)

y = x^2 + 4x - 7 is in the form of y = ax^2+bx+c

where: a = 1, b = 4, c = -7

Plug those a,b values into the formula below

h = -b/(2a)

h = -4/(2(1))

h = -2

This is the x coordinate of the vertex.

Use it to find the y coordinate of the vertex.

y = x^2 + 4x - 7

y = (-2)^2 + 4(-2) - 7

y = -11

The vertex is located at (h,k) = (-2,-11)

We have the template y = a(x-h)^2 + k update to y = (x + 2)^2 - 11 after plugging in a = 1, h = -2, and k = -11.

Give them brainiest ^^^^ (: